Monitoring The Usage of Marine Fuel Oil Aboard Ketapang Gilimanuk Ship - Sarman Sarman; Arief Marwanto; Suryani Alifah (IAES Indonesia Section, 2018)
The development of the shipping industry in Indonesia has continued to increase over the past 10 years due to the sabotage principle. This development can be seen from the increasing number of national vessels. The number of national vessels becomes wider from 6,041 units in 2005 to 24,046 units in 2016. The number of vessels makes monitoring the operational performance of the vessel difficult because each ship has different travel routes. This research made tools that can monitor the performance of ships especially the use of MFO aboard the ship. The sensors used to measure the volume of MFO in the tank on board are HC-SR04 ultrasonic sensors and potentiometer pendulum sensors. The data from the sensor was processed by Arduino Uno microcontroller. This study would compare the performance of ultrasonic sensors and potentiometer pendulum sensors mounted on MFO oil premises. The study was conducted by measuring the position of the ship horizontally, right and left tilted with a slope level of 30 degrees and 45 degrees. The result of this research is that the potentiometer pendulum sensor was better when MFO surface condition was flat with the average of error sensor 1.60%, while HC-SR04 ultrasonic sensor has an average of error for 2.87%. However, on the skewed surface conditions of MFO, the usage of HC - SR04 ultrasonic sensors was better with average of error for 3.21%, while the potentiometer pendulum sensor had an average of error for 8.66%.